Responding to obsolescence in Flash-based net art: a case study on migrating Sinae Kim's Genesis. - Mladentseva, Anna (Journal of the Institute of Conservation, 2022)
Many internet artworks from the mid-1990s to the early 2000s used Adobe Flash technology for creating animated content. However, in the light of recent web standard developments (HTML5), Adobe has stopped supporting Flash and its related tools. The removal of Flash has made those net artworks non-functional and unviewable, including Sinae Kim's Genesis (2001), the focus of this study. Recently proposed emulation- and virtualisation-based strategies are not always suitable, particularly if there is a desire to keep the artwork on the 'live web'. This article outlines an alternative method of migration facilitated by reverse engineering techniques—specifically decompilation—and foregrounds the significance of maintaining online access to the obsolete Adobe Shockwave Flash (SWF) files through the source code. On this premise, the source code is re-imagined as a site for further re-enactment, allowing a departure from its current role as a marker of 'authenticity'.